Reduced vasodilator function following acute resistance exercise in obese women - Franklin, Nina C.; Ali, Mohamed; Goslawski, Melissa; Wang, Edward; Phillips, Shane A. (Frontiers in Physiology, 2014)
Obesity contributes to stress induced impairments in endothelium-dependent vasodilation (EDV), a precursor to atherosclerosis. Since obesity is associated with inflammation and oxidative stress, we sought to determine if a single bout of strenuous weight lifting (SWL) reduces EDV among sedentary obese adults. Participants included 9 obese (OB) (BMI 30.0–40.0 kg/m2) and 8 lean (LN) (BMI 18.5–24.9 kg/m2) sedentary young women. All participants underwent a single bout of SWL using a progressive leg-press protocol. Brachial artery flow-mediated dilation (FMD) (an index of EDV) was determined using ultrasonography before and after SWL. Sublingual nitroglycerin (NTG) was used to determine brachial artery endothelium-independent vasodilation following SWL. Brachial artery FMD was significantly reduced in OB and LN women (LN: 6.4 ± 1.6%, p = 0.22) after SWL. There was no difference in the magnitude of change pre- and post-SWL between groups (OB: −2.4 ± 0.6% and LN: −2.2 ± 1.6%, p = 0.84). Dilation to NTG was lower in OB (21.6 ± 1.3%) compared to LN women (27.6 ± 2.1%, p = 0.02) and associated with body weight (r = −0.70, p = 0.01). These data suggest that EDV is reduced in woman after acute resistance exercise. Dilations to NTG were lower in obese compared to lean woman and associated with body weight suggesting that changes in sensitivity of blood vessels to NO occurs during obesity. These findings may be important for understanding vascular risk following acute exercise in obesity.